2008
DOI: 10.1177/0192513x08324575
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Familial and Environmental Factors on the Adjustment of Immigrants

Abstract: This study examined the impact of family interaction, perceived discrimination, stressful life events, and the hosting country on the adjustment of Israeli and German immigrants. Results show that changes in self-esteem between the 1st year of immigration and 2 and 4 years later were significantly related to family relations: the better the functioning, the greater the improvement. The patterns of relationships in the family, however, only partially explained changes in psychological well-being and language pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 70 publications
3
41
1
Order By: Relevance
“…The number of stressful life events was not statistically related to SWB in our study, despite the available evidence linking negatively stressful life events and SWB in both general (Hammen, 2005;Lantz, House, Mero, & Williams, 2005;Monroe & Harkness, 2005) and immigrant populations (Hovey & Magan, 2002;Slonim-Nevo, Mirsky, Rubinstein, & Nauck, 2009). Although the tendency observed in our data suggested a bivariate negative relationship between stressful life events and SWB (Pearson's coefficients, r 5 À.05), these coefficients were not statistically significant at po.05.…”
Section: Discussioncontrasting
confidence: 91%
“…The number of stressful life events was not statistically related to SWB in our study, despite the available evidence linking negatively stressful life events and SWB in both general (Hammen, 2005;Lantz, House, Mero, & Williams, 2005;Monroe & Harkness, 2005) and immigrant populations (Hovey & Magan, 2002;Slonim-Nevo, Mirsky, Rubinstein, & Nauck, 2009). Although the tendency observed in our data suggested a bivariate negative relationship between stressful life events and SWB (Pearson's coefficients, r 5 À.05), these coefficients were not statistically significant at po.05.…”
Section: Discussioncontrasting
confidence: 91%
“…This indicates the ability of individuals to overcome life's difficulties and challenges by using social support. The three main avenues of social support are the family, social institutions, and peers [12,14,15]. Social support has two essential effects: the main effect of benefitting the individual in regular (not stressful) periods and the buffering effect, which mitigates the negative impact of life stressors on the individual's adjustment during stressful periods.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the country of origin identity becomes of relevance for the immigrants' adjustment after their arrival in the receiving country, when they feel that other people perceive them as aliens and they encounter discrimination (Berry et al, 1987;Eisenstadt, 1954;Tartakovsky & Schwartz, 2001;Winter-Ebmer, 1994). When arriving in Israel, the immigrants from the FSU understand that the receiving society see them as ''Russians'' or ''Ukrainians'' (i.e., as outsiders and not as Israelis), and this feeling of alienation may necessitate the ability to feel a positive connection with their country of origin in order to buffer feelings of rejection and instability, to maintain higher self-worth, and thus promote psychosocial adjustment (Bizman & Yinon, 2001;Slonim-Nevo, Mirsky, Rubinstein, & Nauck, 2009;Tykocinski & Bareket-Bojmel, 2009). Titzmann, Silbereisen, and Schmitt-Rodermund (2007) Russian Jewish immigrant adolescents in Israel found that perceived discrimination was related to increased friendships with other immigrants as opposed to with Israelis.…”
mentioning
confidence: 99%